1998
DOI: 10.1177/002215549804600909
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Differentiation of Both Free 3′-OH and 5′-OH DNA Ends Between Heat-induced Apoptosis and Necrosis

Abstract: S U M M A R YCell death is roughly categorized as either apoptosis or necrosis. For better understanding of the differences in DNA cleavage between them, we performed quantitative analysis of both the 3 Ј-OH and the 5 Ј-OH ends of DNA strand breaks via in situ nick-end labeling (ISEL) combined with transmission electron microscopy (TEM) of both heat-induced apoptosis and necrosis in mouse B-cells derived from a lymphoma cell line. To detect the 5 Ј-OH ends, the 3 Ј-P ends located on the opposite side holding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
28
0
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 28 publications
0
28
0
1
Order By: Relevance
“…Alternatively, PCD activity may have been reduced by the stress-mediated upregulation of heat shock proteins that are known inhibitors of PCD. [6][7][8] A shift from PCD to necrosis occurs in several vertebrate systems in response to temperature, 29,32 other stressors and disease. [33][34][35] A similar pattern in the anemone, a lower invertebrate, suggests that the mechanisms controlling the shift between different forms of cell death in response to stress may be highly conserved.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, PCD activity may have been reduced by the stress-mediated upregulation of heat shock proteins that are known inhibitors of PCD. [6][7][8] A shift from PCD to necrosis occurs in several vertebrate systems in response to temperature, 29,32 other stressors and disease. [33][34][35] A similar pattern in the anemone, a lower invertebrate, suggests that the mechanisms controlling the shift between different forms of cell death in response to stress may be highly conserved.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, DNA fragmentation also occurs in necrosis. 30 For this reason, we paid attention to perform TUNEL staining always under constant conditions of reaction time, reagent concentrations and room temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies using the TUNEL method have cast doubt on its specificity of detecting apoptosis because the TUNEL method detects not only apoptotic cells but also necrotic and mitotic cells (Grasl-Kraupp et al 1995;Sit et al 1997;Wolvekamp et al 1998;Otsuki 2000Otsuki ,2004. The TUNEL method by TEM (TUNEL/TEM) was developed for retrospective studies using archival epoxyresin-embedded materials and enables the morphological discrimination of apoptotic cells among many cell types including necrotic or mitotic cells based on ultrastructural characteristics (Inoki et al 1997;Hayashi et al 1998;Otsuki 2000Otsuki ,2004. To date, several studies of psoriasis have shown that almost all proliferative keratinocytes are TUNEL positive, although psoriasis is a hyperproliferative disease (Laporte et al 2000).…”
mentioning
confidence: 99%